Emergence of spin–charge conversion functionalities due to spatial and time-reversal asymmetries and chiral symmetry - Kondou, Kouta; Otani, Yoshichika (Frontiers in Physics, 2023)
Spin-charge conversion leads to the driving principle of spintronics devices, such as non-volatile magnetic memory and energy harvesting devices from light, sound, and heat to charge current. Recently, controllable spin-charge conversions have emerged in materials with spatial- and time-reversal asymmetry as a new route for efficient manipulation and realization of novel functionalities of future spintronics devices. This article overviews the spin-charge conversion from the fundamental mechanism to the recent research progress in novel materials like topological magnets and atomically layered materials. Additionally, we discuss the chiral organic materials from the viewpoint of a new pathway for the emergence of spin functionalities.